1978
DOI: 10.1055/s-0038-1636604
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Bayes Program for Classification of Coma

Abstract: In previous investigations two additive 5-step scales (Guttman-scales) for »susceptibility to stimulation« and »reactivity« were developed. Both scales have proved very reliable for the measurement of levels of coma. Compared to usual examinations they entail additional effort. The present paper examines the possible prediction of scale-values, using neurological signs which are easier to obtain than the scale scores. A Bayes procedure was developed and. tested. Results from classification demonstrate that rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Bayesian analysis was used to determine the optimal diagnostic criteria for diagnostic peritoneal lavage for abdominal trauma victims (25). Other areas in which Bayesian analysis has been used is the evaluation of electrocardiography (28) and coma (29). Place et al (27) showed the importance of prior probabilities based on age or family history in the evaluation of patients with breast masses using fine-needle aspiration cytology.…”
Section: Applications Of Bayesian Analysis In the Diagnostic Processmentioning
confidence: 99%
“…Bayesian analysis was used to determine the optimal diagnostic criteria for diagnostic peritoneal lavage for abdominal trauma victims (25). Other areas in which Bayesian analysis has been used is the evaluation of electrocardiography (28) and coma (29). Place et al (27) showed the importance of prior probabilities based on age or family history in the evaluation of patients with breast masses using fine-needle aspiration cytology.…”
Section: Applications Of Bayesian Analysis In the Diagnostic Processmentioning
confidence: 99%